The Influence of Financial Stress and Conformity on the Academic Achievement of Students in Kupang City - Kostantia Klara Anjalika Hadjon; Hedwigh Hendrikus Temai Lejap; Maria Bernadethe Mawarni Gelu Wutun (AKSIOMA : Jurnal Manajemen, 2026)
The urgency of this research is the high rate of college dropouts due to economic factors and the academic achievement of students who have not reached ideal conditions. The purpose of the study is to determine the influence of financial stress and conformity on the academic achievement of students in Kupang City. The population in this study is all students in Kupang City. The sample in this study is 150 respondents. Data collection uses a questionnaire through Google Forms. Data analysis uses descriptive statistical analysis and inferential statistical analysis. The results of the descriptive analysis described the Financial Stress variable of 65.41% (Medium), the conformity variable of 70.13% (High), and the academic achievement variable of 72.13% (High), all of which were in the good category. The results of hypothesis testing showed that the financial stress variable partially had a negative and significant effect on academic achievement. Conformity partially has a positive and significant effect on academic achievement. Financial stress and conformity simultaneously have a significant effect on academic achievement. The resulting Coefficient of Determination (R2) value explains the contribution of the influence of the independent variable to the dependent variable by 28.2%, while the remaining 71.8% is influenced by other variables that are not included in this study.